Interventions before consultations for helping patients address their information needs. - Kinnersley, P; Edwards, A; Hood, K; Cadbury, N; Ryan, R; Prout, H; Owen, D; Macbeth, F; Butow, P; Butler, C (2007)
BACKGROUND: Patients often do not get the information they require from doctors and nurses. To address this problem, interventions directed at patients to help them gather information in their healthcare consultations have been proposed and tested. OBJECTIVES: To assess the effects on patients, clinicians and the healthcare system of interventions which are delivered before consultations, and which have been designed to help patients (and/or their representatives) address their information needs within consultations. SEARCH STRATEGY: We searched: the Cochrane Central Register of Controlled Trials (CENTRAL, The Cochrane Library (issue 3 2006); MEDLINE (1966 to September 2006); EMBASE (1980 to September 2006); PsycINFO (1985 to September 2006); and other databases, with no language restriction. We also searched reference lists of articles and related reviews, and handsearched Patient Education and Counseling (1986 to September 2006). SELECTION CRITERIA: Randomised controlled trials of interventions before consultations designed to encourage question asking and information gathering by the patient. DATA COLLECTION AND ANALYSIS: Two researchers assessed the search output independently to identify potentially-relevant studies, selected studies for inclusion, and extracted data. We conducted a narrative synthesis of the included trials, and meta-analyses of five outcomes. MAIN RESULTS: We identified 33 randomised controlled trials, from 6 countries and in a range of settings. A total of 8244 patients was randomised and entered into studies. The most common interventions were question checklists and patient coaching. Most interventions were delivered immediately before the consultations.Commonly-occurring outcomes were: question asking, patient participation, patient anxiety, knowledge, satisfaction and consultation length. A minority of studies showed positive effects for these outcomes. Meta-analyses, however, showed small and statistically significant increases for question asking (standardised mean difference (SMD) 0.27 (95% confidence interval (CI) 0.19 to 0.36)) and patient satisfaction (SMD 0.09 (95% CI 0.03 to 0.16)). There was a notable but not statistically significant decrease in patient anxiety before consultations (weighted mean difference (WMD) -1.56 (95% CI -7.10 to 3.97)). There were small and not statistically significant changes in patient anxiety after consultations (reduced) (SMD -0.08 (95%CI -0.22 to 0.06)), patient knowledge (reduced) (SMD -0.34 (95% CI -0.94 to 0.25)), and consultation length (increased) (SMD 0.10 (95% CI -0.05 to 0.25)). Further analyses showed that both coaching and written materials produced similar effects on question asking but that coaching produced a smaller increase in consultation length and a larger increase in patient satisfaction. Interventions immediately before consultations led to a small and statistically significant increase in consultation length, whereas those implemented some time before the consultation had no effect. Both interventions immediately before the consultation and those some time before it led to small increases in patient satisfaction, but this was only statistically significant for those immediately before the consultation. There appear to be no clear benefits from clinician training in addition to patient interventions, although the evidence is limited. AUTHORS' CONCLUSIONS: Interventions before consultations designed to help patients address their information needs within consultations produce limited benefits to patients. Further research could explore whether the quality of questions is increased, whether anxiety before consultations is reduced, the effects on other outcomes and the impact of training and the timing of interventions. More studies need to consider the timing of interventions and possibly the type of training provided to clinicians.